PERGESERAN MAKNA MITOS NILAI SPIRITUAL KEBUDAYAAN ONDEL-ONDEL PADA KEPERCAYAAN MASYARAKAT BETAWI ZAMAN DAHULU DAN ZAMAN SEKARANG - Lazizah Akmaliyah; Zahratul Jannah Zulfa; Nikmah Rochmawati (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2021)
Ondel-ondel is a cultural performance of the Betawi people passed down from generation to generation. However, the problem that occurs is that along with the development of the era, ondel-ondel is no longer a sacred object and is no longer used for ritual offerings and the loss of cultural values of the ancestors. The purpose of making this journal is to find out the shift in the meaning of the ondel-ondel cultural myth to the beliefs of the people of Jakarta. The method used in this study uses a qualitative approach and data collection techniques use interview techniques, observation and analysis of various journals or literature studies. The subject of this research was conducted on 4 people, namely a number of the Jakarta community about their views on the shift in the meaning of the myth of ondel-ondel art. In this day and age, ondel-ondel shows are very easy to find, especially on roadside areas in Jakarta. Unlike the old days, ondel-ondel was only displayed when there were certain events such as a traditional Betawi wedding. The result of this research is that there are differences and shifts in the meaning of ondel-ondel cultural myths. In ancient times ondel-ondel was only displayed during certain events. And people in ancient times tend to still believe in the existing ondel-ondel cultural myths. Unlike the current era, ondel-ondel is used as a means of getting money. The benefit of this research is to find out what values have been lost from previous cultures and be able to take good positive values taught in previous cultures without taking the negative values found in the past culture. It is enough to make historical knowledge to remember existing history. This study concludes that there has been a shift in meaning in the myth of ondel-ondel culture and sadly it occurs due to the pressure of economic factors.